Learner satisfaction-based research on the application of artificial intelligence science popularization kits - Ling, Yingfei; Jin, Zhou; Li, Yingxin; Huang, Jieya (Frontiers in Psychology, 2022)
The use of artificial intelligence science kits in the maker course has promoted the rapid development of maker course. To this end, based on the opportunity of the comprehensive implementation of the action plan for promoting the development of a new generation of artificial intelligence in Zhejiang Province (2019-2022), this study first combined literature analysis and questionnaire results with semi-structured interviews, and used SPSS 24.0 to conduct Person correlation analysis and regression analysis to explore the factors influencing students' satisfaction with the use of AI science kits in education. Then, the application idea of "based on the quality of the kit, focusing on improving human-computer interaction, 'student-centered' as a strategy, and improving the relevance of the curriculum" was proposed. The research results of the article can provide theoretical reference for the construction, teaching practice and organization management of the creative course system using AI science kits.